“No Plastic Bag Day” & Environmental Behavior in Malaysia - Yeo, Keong Seong (2013)
Environment deterioration issue is a prominent phenomenon globally. The background of the study covering the environment experiencing a reversion and the situation is getting worse. The effects of such environmental issues have not only affected the climate changes, rainforests, natural disasters as well as individual lifestyle. One of the significant wastage which contributed to environmental deterioration is caused by the not biodegradable plastic bag. However, plastic bag wastage issues soon arouse public awareness and persuade people to behave green at every aspect, from the working environment to housing. This study consists of the after effect of the “No Plastic Bag Day” organized by Malaysian government aimed at reducing the deterioration effect brought about by plastic bag. The majority of the studies have only examined the phenomenon of the plastic bag ban in abroad. Therefore, the unveiling of “No Plastic Bag Day” by the Malaysia government provides an opportunity to examine the phenomenon based-on Malaysian perspective. The purpose of this research is to investigate on Malaysian values, awareness and attitude towards “No Plastic Bag Day”. It also investigates how this event changes the consumers’ behavior every Saturday. This research is based on the quantitative research approach. The study will analyze 250 respondents from around the Kiang Valley for over a period of 2months. The using of Environmental Behavior (theoretical lens) will be analyzed from different perspective and it will revolve around the literature review. In this research, PLS modeling approach and SPSS (frequency distribution, descriptive analysis, reliability analysis and multiple regression) will be used to analyze for investigating the awareness level Malaysian have concerning “No Plastic Bag Day” policy and which of the factors influence the most in environmental behavior development. The empirical analysis using PLS unveiled that Eco literacy, Perceived Behaviors and Subjective Norms have a significant relationship to environmental behavior development. The awareness and perception towards this event is significant as well.